Health profiles of foreigners attending primary care clinics in Malaysia - Ab Rahman, N.; Sivasampu, S.; Mohamad Noh, K.; Khoo, E.M. (BioMed Central, 2016)
Background: The world population has become more globalised with increasing number of people residing in another country for work or other reasons. Little is known about the health profiles of foreign population in Malaysia. The aim of this study was to provide a detailed description of the health problems presented by foreigners attending primary care clinics in Malaysia. Methods: Data were derived from the 2012 National Medical Care Survey (NMCS), a cross sectional survey of primary care encounters from public and private primary care clinics sampled from five regions in Malaysia. Patients with foreign nationality were identified and analysed for demographic profiles, reasons for encounter (RFEs), diagnosis, and provision of care. Results: Foreigners accounted for 7.7 % (10,830) of all patient encounters from NMCS. Most encounters were from private clinics (90.2 %). Median age was 28 years (IQR: 24.0, 34.8) and 69.9 % were male. Most visits to the primary care clinics were for symptom-based complaints (69.5 %), followed by procedures (23.0 %) and follow-up visit (7.4 %). The commonest diagnosis in public clinics was antenatal care (21.8 %), followed by high risk pregnancies (7.5 %) and upper respiratory tract infection (URTI) (6.8 %). Private clinics had more cases for general medical examination (13.5 %), URTI (13.1 %) and fever (3.9 %). Medications were prescribed to 76.5 % of these encounters. Conclusions: More foreigners were seeking primary medical care from private clinics and the encounters were for general medical examinations and acute minor ailments. Those who sought care from public clinics were for obstetric problems and chronic diseases. Medications were prescribed to two-thirds of the encounters while other interventions: laboratory investigations, medical procedures and follow-up appointment had lower rates in private clinics. Foreigners are generally of young working group and are expected to have mandatory medical checks. The preponderance of obstetrics seen in public clinics suggests a need for improved access to maternal care and pregnancy related care. This has implication on policy and health care provision and access for foreigners and future studies are needed to look into strategies to solve these problems.